Designing food safety and equipment reliability through maintenance engineering - Riccetti, Sauro (Boca Raton : CRC Press, 2014)
'Existing maintenance engineering techniques pursue equipment reliabiltiy with a focus on minimal costs, but in the food industry, food safety is the most critical issue. This book identifies how to ensure food product safety through maintenance engineering in a way that produces added value and generates real profits for your organization. Integrating food safety techniques with reliability and maintenance ingineering techniques, Designing food safety and equipment reliability through maintenance engineering details a maintenance design process that captures all conceivable critical factors in food manufacturing lines. While maintenance engineering normally starts with equipment reliability, this book starts wiht product safety to identify criticalities and maintenance solutions.'--Back cover.
'A Productivity Press Book'
Includes bibliographical references (pages 371-374) and index.
Keywords: Food industry and trade -- Safety measures; Food processing machinery -- Reliability; Reliability (Engineering).; Maintainability (Engineering).; Safety factor in engineering